Enseignement du français à distance en Nouvelle-Zélande : modalités, utilité et limites du numérique - Grenaudier-Klijn FM-L; Perthuis D (Universidad Complutense de Madrid)
Several technological tools are used in the teaching of French in distance mode at Massey University, New Zealand. They play a part in the dissemination of the teaching material, the evaluation of oral and written activities, interactions between students and teaching staff, and in the individual monitoring of students. More schematically, these tools allow for a reconciliation of learners’ autonomy and teachers’ supervision. The empirical study that follows seeks to analyse two types of “encounters” between learners and teachers: weekly online tutorials using AdobeConnect, whose emphasis is on synchronic oral communication; individual weekly written activities submitted by students on Moodle/ Stream which are informally marked in turn a-synchronically. In so doing, we will examine the manner in which these digital tools are used by the various participants, but also the difficulties and limitations inherent in the use of digital technology in the teaching and learning of French as a second language.
Keywords: Moodle/Stream; AdobeConnect; Distance teaching; New Zealand; FLE (French as a Foreign Language)